Patterns of utilisation of reference vessels in the library of the Faculty of Education, Misurata University, from the point of view of faculty members in the faculty. (Journal of Academic Research, 2024)
The study dealt with the issue of benefiting from reference vessels in university libraries, specifically in the library of the Faculty of Education, Misurata University, from the point of view of faculty members in the college The study aims to: identify the reality of the general and specialised reference vessels in the library of the Faculty of Education at Misurata University in terms of types and numbers, and to know the ways to benefit from the general and specialised reference vessels in the library under study from the point of view of faculty members, and to know the most important problems and obstacles that hinder faculty members from benefiting from the general and specialised reference vessels in the landfill subject of the study according to the required form The study relied on the case study methodology in its preparation The study concluded several results, the most important of which were: the reference vessels in the library of the Faculty of Education, Misurata University, are very old in most of them and need to be updated, and the number of copies of the reference containers in the library under study is very small and do not suit the size of the beneficiaries in general and faculty members in particular, and the study also noted several recommendations, the most important of which were: Work to update the reference containers in the library of the Faculty of Education at Misurata University in order to meet the needs of the beneficiaries in general and faculty members in particular, Providing the appropriate numbers of reference containers to be used for all beneficiaries, especially faculty members